PERANAN LINGKUNGAN FISIK YANG KONDUSIF DALAM MENINGKATKAN KINERJA GURU MADRASAH IBTIDAIYAH - Suriani Nur (Institut Agama Islam Negeri (IAIN) Bone, 2018)
The essence of learning is an interaction process to the situation around the learner as an individual. Learning is a system that has interconnectedness with one another. The learning process will take place well if there are reliable teachers who have good performance in carrying out their duties to transfer knowledge and moral values good for learners. The performance of teachers in performing their duties as instructors is determined by various factors either from within himself or from outside himself, one of the factors affecting teacher performance is the physical environment of madrasah. The physical environment of the madrasah will affect the madrasah climate and will impact on teacher performance. The physical environment of a good madrasah provides beauty, comfort, security and calm so that teacher performance can improve and produce a quality generation.